The influence of extratropical Atlantic Ocean region on wet and dry years in North-Northeastern Brazil - de Albuquerque Cavalcanti, Iracema F. (Frontiers in Environmental Science, 2015)
The rainy season of north-Northeastern Brazil (NE), one of the tropical regions with the largest rainfall interannual variability, is associated with the Intertropical Convergence Zone (ITCZ) influence, which is located in the southermost position during this season (March-April-May). However, there is a large interannual variability in the ITCZ position, associated with atmospheric and oceanic anomalies, responsible for dry or wet years in the region. Besides the tropical Pacific Sea Surface Temperature (SST) anomalies and the Tropical Atlantic SST gradient influences on this variability, extratropical atmospheric influences are identified over the North and South Atlantic. Composites of cases with anomalous precipitation during the middle of the rainy season (April) indicate the El Niño-Southern Oscillation (ENSO) features and northern and southern Atlantic atmospheric anomalies in December-January-February (DJF). When El Niño and La Niña years are removed from the composites of dry and wet cases, respectively, the centers of action over the extratropical North Atlantic in DJF remain, and features of extratropical South Hemisphere become more evident. The tropical SST dipole is still present with inverted signs in each case, consistent with the NE precipitation anomalies. The main mode of variability in the Southern Hemisphere (South Annular Mode) and in the Northern Hemisphere (North Annular Mode) is present in DJF during the dry cases. These annular patterns occur in the composites of Northeast Brazil precipitation anomalies including or excluding ENSO years. Therefore, besides ENSO relations with SAM discussed in previous studies, another connection exists over the South Atlantic, linking anomalies between high and tropical latitudes. The precipitation anomalies over NE have contributions of the two extratropical Atlantic hemispheres regions. The atmospheric anomalies observed in the pre-rainy season can be a helpful tool in monitoring the North Northeastern B